2011
DOI: 10.18061/1811/51204
|View full text |Cite
|
Sign up to set email alerts
|

Musicians' Attitudes to Musical Influence

Abstract: This article discusses responses to an online survey on the topic of musical influence. 119 participants took part, answering both quantitative (five point Likert scale) and qualitative questions. A rich set of data was collected, which is summarized and analyzed in this paper. The primary research aim was to discover a good opinion base concerning issues of musical influence, to help illuminate some existing theories of influence, and in turn to inform further research directions. General trends observed incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…8 Corpus-based composition systems have an advantage in that they make absolutely explicit what influences they require. However, study of musicians' attitudes to influence has shown that humans are not overly anxious about influence (Collins, 2011). A richly creative AI may need to forget the circumstances of its learning about a particular training example, so as not to be overly burdened by the weight of history.…”
Section: Listening To Everythingmentioning
confidence: 99%
“…8 Corpus-based composition systems have an advantage in that they make absolutely explicit what influences they require. However, study of musicians' attitudes to influence has shown that humans are not overly anxious about influence (Collins, 2011). A richly creative AI may need to forget the circumstances of its learning about a particular training example, so as not to be overly burdened by the weight of history.…”
Section: Listening To Everythingmentioning
confidence: 99%
“…When machines are involved in making musical judgments, the volume of reference can potentially scale up to even more depressing or exciting a degree, depending on a creator's perspective. In the main, positive benefits of historical awareness and the potential for new "database music" may be hoped to dominate: A recent online study of musicians' attitudes to influence found no strong evidence for any 'anxiety of influence' and most musicians in the survey welcomed a sense of musical history and culture [Collins 2011].…”
Section: Algorithmic Critic Technologymentioning
confidence: 99%
“…For example, in a large survey of 244 respondents, Creech et al (2008) corroborated that important factors of influence for classical musicians included teachers, parents, peers and specific musical events, and for non-classical musicians factors also included the influence of well-known performers (p. 226). In another large study of 119 respondents, Collins (2011) examined issues of musical influence and reported that, although advanced musicians nurture, on the whole, a positive attitude towards influence (pp. 103, 118), the sources of influence can change over time (p. 113).…”
Section: Introductionmentioning
confidence: 99%